Direct and inverse theorems on approximation of functions defined on a sphere in the space S (p,q)(σ m) - Lasuriya, R. A. (Ukrains’kyi Matematychnyi Zhurnal, 2007)
We prove direct and inverse theorems on the approximation of functions defined on a sphere in the space S (p,q)(σ m), m > 3, in terms of the best approximations and modules of continuity. We consider constructive characteristics of functional classes defined by majorants of modules of continuity of their elements.